Recommendations for pathologic practice using digital pathology: consensus report of the Korean Society of Pathologists - Yosep Chong; Dae Cheol Kim; Chan Kwon Jung; Dong-chul Kim; Sang Yong Song; Hee Jae Joo; Sang-Yeop Yi; Medical Informatics Study Group of the Korean Society of Pathologists (Journal of Pathology and Translational Medicine, 2020)
Digital pathology (DP) using whole slide imaging (WSI) is becoming a fundamental issue in pathology with recent advances and the rapid development of associated technologies. However, the available evidence on its diagnostic uses and practical advice for pathologists on implementing DP remains insufficient, particularly in light of the exponential growth of this industry. To inform DP implementation in Korea, we developed relevant and timely recommendations. We first performed a literature review of DP guidelines, recommendations, and position papers from major countries, as well as a review of relevant studies validating WSI. Based on that information, we prepared a draft. After several revisions, we released this draft to the public and the members of the Korean Society of Pathologists through our homepage and held an open forum for interested parties. Through that process, this final manuscript has been prepared. This recommendation contains an overview describing the background, objectives, scope of application, and basic terminology; guidelines and considerations for the hardware and software used in DP systems and the validation required for DP implementation; conclusions; and references and appendices, including literature on DP from major countries and WSI validation studies.